After Legalization: Understanding the Future of Marijuana Policy - Jon Walker (FDL Writers Foundation, 2014)
After Legalization: Understanding the Future of Marijuana Policy is a groundbreaking new book examining how legal marijuana will likely be treated in the United States two decades from now.